2012
DOI: 10.1080/03601234.2012.669337
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of some heavy metals in organically grown primitive, old and modern wheat genotypes: Implications for human health

Abstract: The concentration of six HMs (Cd, Cr, Co, Pb, Hg and Ni) was analysed in 321 organically grown winter and spring wheat genotypes from six genotype groups, i.e. selections, old landraces, primitive wheat, spelt, old cultivars and cultivars. Also the potential risk of individual toxic HM to human health was estimated by using the Hazard Quotient (HQ). Significantly the lowest grain concentration of Cd was found in primitive wheat as compared to all other investigated genotype groups. Intake of HM by consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…One explanation for higher levels of heavy metals in conventional than organic crops and crops based food might be the higher levels of Cd, copper and Zn in inorganic fertilizers that commonly have been used, although presence of heavy metals in conventional fertilizers has been reduced during recent years [139]. Similarly as for the nutritional compounds discussed above, a large variation in heavy metal accumulation among genotypes, also when organically grown, have been reported [140]. …”
Section: Additional Human Health Related Issues In Crops—chemicalsmentioning
confidence: 99%
“…One explanation for higher levels of heavy metals in conventional than organic crops and crops based food might be the higher levels of Cd, copper and Zn in inorganic fertilizers that commonly have been used, although presence of heavy metals in conventional fertilizers has been reduced during recent years [139]. Similarly as for the nutritional compounds discussed above, a large variation in heavy metal accumulation among genotypes, also when organically grown, have been reported [140]. …”
Section: Additional Human Health Related Issues In Crops—chemicalsmentioning
confidence: 99%
“…e volume of cooled mixture was adjusted to 100 ml by adding water. e analyses of minerals and heavy metal content were made using an ICP-OES, Optima 8300, and PerkinElmer [40] at Lund University following methods described in [41,42].…”
Section: Determination Of Mineral Elements and Heavy Metalmentioning
confidence: 99%
“…Wheat belongs to non-hyperaccumulators, but still accumulates high amount of heavy metals, especially in grains [10]. Besides, plant genotypes differ in their uptake, translocation, accumulation of trace metals [4], and similar phenomenon was observed in wheat plants and asparagus bean cultivars [9,22]. Recently, Hansi et al found, in lab, that the concentration of Cu in barley shoot would reduce with increasing planting density [8].…”
Section: Introductionmentioning
confidence: 86%